Relationship between lifestyle and metabolic factors and carotid atherosclerosis: A survey of 47,063 fatty and non-fatty liver patients in China - Zhang, Chun; Wang, Jiangang; Ding, Siqing; Gan, Gang; Li, Lijun; Li, Ying; Chen, Zhiheng; Duan, Yinglong; Xie, Jianfei; Cheng, Andy S. K. (Frontiers in Cardiovascular Medicine, 2022)
Background and aims Carotid atherosclerosis and stenosis are common lesions of the artery wall that form the basis of cardiovascular events. Compared with coronary atherosclerosis, few studies have explored the influencing factors of carotid atherosclerosis. The aim of this study was to explore the influencing factors of carotid atherosclerosis and carotid stenosis without and with fatty liver disease (FLD). Methods A total of 47,063 adults were recruited for this cross-sectional study. The color Doppler ultrasound, including metabolic factors and lifestyle surveys, was used to determine whether the participants had FLD and carotid artery disease. Multiple logistic regression was used to investigate the influencing factors of lifestyle and metabolism of carotid atherosclerosis and stenosis in the participants with and without FLD. Results In participants without FLD, current alcohol consumption (OR: 0.749, 95% CI: 0.588) and hip circumference (OR: 0.970, 95% CI: 0.961, 0.979) were the main protective factors for carotid atherosclerosis. Systolic blood pressure (OR: 1.022, 95% CI: 1.019, 1.025) and diastolic blood pressure (OR: 1.005, 95% CI: 1.001, 1.010), elevated fasting blood glucose (OR: 1.012, 95% CI: 1.005, 1.019), and non-sedentary behavior (OR: 1.084, 95% CI: 1.014, 1.160) were the main risk factors for carotid atherosclerosis. Hip circumference (OR: 0.932, 95% CI: 0.910, 0.954) and low-density lipoprotein (OR: 0.979, 95% CI: 0.964, 0.994) were protective factors for carotid stenosis. Smoking (OR: 3.525, 95% CI: 1.113, 11.169) and unqualified exercise (OR: 1.402, 95% CI: 1.083, 1.815) were risk factors for carotid stenosis. In participants with FLD, smoking (OR: 0.827, 95% CI: 0.703, 0.973) and hip circumference (OR: 0.967, 95% CI: 0.958, 0.977) were the main protective factors for carotid atherosclerosis. BMI 18.5–23.9 (OR: 1.163, 95% CI: 1.002, 1.351), non-sedentary behavior (OR: 1.086, 95% CI: 1.009, 1.168), and waist circumference (OR: 1.030, 95% CI: 1.022, 1.038) were the main risk factors for carotid atherosclerosis. Conclusion Based on a large-sample check-up population in China, this study investigated the influencing factors of carotid atherosclerosis and carotid stenosis in fatty liver and non-fatty liver patients and explored the influencing factors of metabolism and lifestyle, which were mainly focused on exercise, sedentary behavior, smoking, alcohol consumption, hip circumference, and blood pressure.